Alcohol dehydrogenase expression patterns in normal prostate, benign prostatic hyperplasia, and prostatic adenocarcinoma in African American and Caucasian men. Issue 6 (8th February 2022) - Stamis, Sarah A.; Heath, Elisabeth I.; Lucas, Steven; Boerner, Julie; Slusher, Leslie B.
Abstract: Background: In situ metabolism of ethanol by alcohol dehydrogenases (ADHs) contributes to oxidative damage of cells and DNA and has been linked to carcinogenesis in numerous epithelial tissues. The goal of this study was to determine expression patterns of ADH1 and ADH7 isozymes in normal, hyperplastic (benign prostatic hyperplasia [BPH]) and neoplastic (prostate cancer [PCa]) prostate. Furthermore, racial differences in ADH expression between African Americans and Caucasians were investigated. Methods: ADH expression patterns were characterized by density analysis of ADH immunohistochemistry ( n = 21) and real‐time RT‐PCR of total RNAs by laser‐capture microdissection ( n = 10) and whole tissue formalin‐fixed paraffin embedded prostate biopsies ( n = 63). Results: ADH protein is found in normal prostate and is primarily associated with glandular epithelium. Transcripts of ADH1B are suppressed in PCa compared to BPH ( p = 0.0095). Racial differences in ADH7 transcripts exist between African American and Caucasian men. A total of 57.6% of biopsies from African American prostates have detectable ADH7 messenger RNA (mRNA) transcripts compared to the 13.3% of Caucasian prostate biopsies with detectable transcripts ( p = 0.0005). This increased frequency of detection contributes to higher mean ADH7 mRNA transcript levels in African Americans ( p = 0.001). Conclusions: To our knowledge this study is the first to report downregulation of ADH1B in neoplastic prostate at the transcriptional level, suggesting protective regulatory functions. ADH7 transcripts were not detectable in all samples and was found in higher frequency and amount in our African American samples. Racial differences in ADH7 within the prostate is a novel finding and should be investigated further.